Effect of virtual reality-based exercise intervention on sleep quality in children with acute lymphoblastic leukemia and healthy siblings: A randomized controlled trial - Tanrıverdi, Müberra; Çakır, Erkan; Akkoyunlu, Muhammed Emin; Çakır, Fatma Betül (Cambridge University Press, 2022)
Objective Sleep is one of the important measurements of the quality of life for children especially suffering from a chronic illness such as cancer. Our aim was to determine the changes in sleep quality and to investigate the effect of virtual reality-based exercise (VRBE) approaches on sleep in patients with acute lymphoblastic leukemia (ALL) off treatment. Method The participants (ALL and healthy siblings) were evaluated for sleep quality with polysomnography and "Children's Sleep Habit Questionnaire" before and after 12 weeks. The study randomized into two groups: an exercise group who received VRBE in two days in a week, 45 min of each session for 12 weeks and an control group who were managed with supportive measures. The VRBE comprised of aerobic exercise in four different games by Nintendo Wii Fit Plus (R). Results This randomized controlled trial was carried out on 38 participants. Before intervention, ALL patients (n = 24) and healthy siblings (n = 14) had similar sleep quality in terms of polysomnography and Children's Sleep Habit Questionnaire findings. After intervention, total time asleep (p = 0.023), respiratory disturbance index of hypopnea (p = 0.005), apnea/hypopnea index (p = 0.008), and number of apnea (p = 0.028) statistically significant improved. Significance of results Patients with ALL off treatment had similar values of sleep quality with healthy siblings. Novel types of exercises like VRBE have positive effects on sleep disorders in children with ALL and also healthy siblings. Future studies are needed comparing the different types of interventions.
Keywords: Acute Lymphoblastic Leukemia; Exercise Therapy; Pediatrics; Sleep Disorders; Virtual Reality